Basic dental sciences as the foundations for clinical practice - Quispe-Salcedo, Angela (2021)
Careers in the area of health sciences combine the acquisition of basic knowledge and specific skills for clinical performance from the early stages of professional training. In the case of dentistry, these skills are extremely complex, which implies that the student has adequate prior knowledge of the structures of the oral cavity and its physiology.